Historical Review of Smallholder Coffee Farmers Population in Kayumas Village, Situbondo Regency - Izzah, Latifatul; Rochwulaningsih, Yety; Krisnadi, IG; Hartanto, Denny Antyo; Sampurna, Insan Cita (Indonesian Historical Studies, 2023)
This study discusses the historical context of the existence of community coffee farmers in Kayumas Village, Arjasa District, Situbondo Regency, starting in 1883 until the formation of a coffee farmer group in 2018. Based on the historical research using primary and secondary sources, this study informs that before Persil Kayumas were rented by a Dutch investor named H. H. van Kol and his colleague J. C. Egter van Wissekerke in 1883, there were already some residents who were growing Arabica coffee. Arabica coffee cultivation was ultimately carried out from generation to generation, because farmers knew that the market for Arabica coffee was higher than products outside of coffee, such as ginger, tobacco, and so on. It was proven that in 2018, eight coffee farmer groups consisting of 410 farmers were formed.